The Effect of Corporate Governance Attributes on Risk Management Practices of Nepalese Commercial Banks - Dhital, Aagya; Phuldel, Anil; Bishwas, Anju; Timalsina, Bibek; Shrestha, Darbin; Pangeni, Dikshu; Pradhan, Radhe Shyam (Nepalese Journal of Finance, 2024)
The study examines the effect of corporate governance attributes on risk management practices of Nepalese commercial banks. Non-performing loan and operational risk are selected as the dependent variables. The selected independent variables are board size, board diversity, audit committee, risk management committee, board meetings, and leverage. The study is based on secondary data of 15 commercial banks with 105 observations for the period from 2015/16 to 2021/22. The data were collected from Banking and Financial Statistics published by Nepal Rastra Bank, publications and websites of Nepal Rastra Bank (NRB) and annual reports of the selected commercial banks. The correlation coefficients and regression models are estimated to test the significance and importance of corporate governance on the risk management practices of Nepalese commercial banks.The study showed that risk management committee has a negative impact on non-performing loan and operational risk. It implies that increase in number of directors in risk management committee leads to decrease in non-performing loan and operational risk. Similarly, audit committee size has a negative impact on non-performing loan and operational risk. It implies that increase in audit committee size leads to decrease in non-performing loan and operational risk. However, leverage ratio has a positive impact on operational risk. It means that increase in leverage ratio leads to increase in operational risk. Similarly, board meeting has a positive impact on non-performing loan and operational risk. It shows that increase in board meeting leads to increase in non-performing loan and operational risk. Similarly, board diversity has a positive impact on non-performing loan and operational risk. It implies that increase in female board directors leads to increase in non-performing loan and operational risk.